Utilization of Instagram Social Media by Account @Tamanwisatagenilagit as A Promotion Media in Increasing Visitors 'Interest of Taman Geni Langit - Mafiroh, Fauzia (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstrak: Geni Langit Tourism Park is a tourist spot located in one of Magetan regencies. This tourist park offers natural scenery combined with photo spots that make this park visited by many tourists. From the description above, the researcher is interested in conducting research on the use of Instagram social media by Geni Langit Tourism Park. This study uses a descriptive type of research with a qualitative approach, namely by describing how the use of Instagram social media by the @tamanwisatagenilangit account in increasing visitor interest. Researchers got data from observations, interviews and documentation. From the research results, conclusions can be drawn: first, the use of Instagram social media by the @tamanwisatagenilangit account is to use several Instagram features, including (1) photo title or caption, (2) Hashtag, (3) Comments (4) Mentions (5) Geotag . Second, based on the results of observations and interviews with several visitors, Instagram social media is quite effective in increasing visitor interest. This is evidenced by the statement of visitors who know the many photo posts with the Instagramable concept from the @tamanwisatagenilangit account.